The Catholic Baptism Fulfills the Longing for Salvation at Ruwatan : Pastoral Circle Approach Overview - Antonius Koko Kristanto; E.P.D. Martasudjita (Journal of Asian Orientation in Theology, 2022)
Javanese Catholic people live in the midst of Javanese culture with its traditions that are still preserved. Out of these traditions, the Javanese people still keep the ruwatan ceremony. Javanese Catholics often question whether or not ruwatan is permissible according to the teachings of the Catholic Church. In this particular topic, the theological question arises regarding whether it is still necessary to seek salvation through rituals, while salvation has been fully accomplished through Jesus Christ and received in the Sacrament of Baptism. In answering this theological problem, the writer uses the pastoral circle method from the theory of Joe Holland Peter Henriot. Meanwhile, to analyze the ruwatan ritual, the writer uses Victor Turner’s theory regarding the three stages of the rite of passage.